2018
DOI: 10.7556/jaoa.2018.108
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Low Back and Posterior Pelvic Pain During and After Pregnancy Using OMT

Abstract: There was no mention of the American Osteopathic Association Guidelines for Osteopathic Manipulative Treatment (OMT) for Patients With Low Back Pain, 3 which strongly recommends OMT for patients with acute or chronic LBP. However, despite these limitations, this study clearly sheds light on the substandard care of LBP, raises concerns about what percentage of DOs comply with the American Osteopathic Association's guidelines, and brings into question how many patients have access to recommended care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Several complementary therapies such as acupuncture, aromatherapy, and reflexology have been studied as well. One study of 191 women found 85% of women felt that complementary therapies were helpful in the reduction of pelvic pain symptoms in pregnancy 49,69 . In several systematic review articles, it was found that complementary therapies such as massage and chiropractic and osteopathic manipulations showed little to no difference in outcomes of decreased pain or increased quality of life when compared with traditional support 46,50,70–74 .…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Several complementary therapies such as acupuncture, aromatherapy, and reflexology have been studied as well. One study of 191 women found 85% of women felt that complementary therapies were helpful in the reduction of pelvic pain symptoms in pregnancy 49,69 . In several systematic review articles, it was found that complementary therapies such as massage and chiropractic and osteopathic manipulations showed little to no difference in outcomes of decreased pain or increased quality of life when compared with traditional support 46,50,70–74 .…”
Section: Managementmentioning
confidence: 99%
“…6,45,46,48 Current treatment regimens increasingly utilize stabilizing exercises and complementary therapies, such as acupuncture, with limited evidence to support improvements. 49,50 Surgical interventions are rarely indicated. 51…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the evidence of positive effects of non-surgical and non-pharmacological treatments, such as physiotherapeutic interventions, acupuncture, or osteopathic manipulations (Gutke et al, 2015;Gallo-Padilla et al, 2016;Ray-Griffith et al, 2018;Smith et al, 2018;Cerritelli et al, 2020), the use of drugs for pain relief (e.g., low-dose aspirin, acetaminophen, non-steroidal anti-inflammatory drugs, and opioids) during pregnancy is still very common (Ray-Griffith et al, 2018). These therapies can affect fetal neurodevelopment: the increase prescriptions for opioids during pregnancy, for example, correlates to an increased incidence of neonatal abstinence syndrome (NAS), resulting in sleeping and feeding difficulties, as well as a dysregulation in newborns' CNS (Pryor et al, 2017;Ray-Griffith et al, 2018).…”
Section: Maternal Painmentioning
confidence: 99%